2016
DOI: 10.1126/scitranslmed.aad6066
|View full text |Cite
|
Sign up to set email alerts
|

Targeted BMI1 inhibition impairs tumor growth in lung adenocarcinomas with low CEBPα expression

Abstract: Lung cancer is the most common cause of cancer deaths. The expression of the transcription factor C/EBPa (CCAAT/ enhancer binding protein a) is frequently lost in non-small cell lung cancer, but the mechanisms by which C/EBPa suppresses tumor formation are not fully understood. In addition, no pharmacological therapy is available to specifically target C/EBPa expression. We discovered a subset of pulmonary adenocarcinoma patients in whom negative/low C/EBPa expression and positive expression of the oncogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 50 publications
7
49
0
Order By: Relevance
“…More importantly, diminished Bmi1 levels reduced the self-renewal capacity of CSCs, which in turn correlated with lowered tumourigenic potential in vitro and in vivo. In keeping with the original observations, cells treated with a Bmi1 inhibitor became more apoptotic 77,[81][82][83] and underwent cell cycle arrest at G 0 phase. 81,82 Collectively, these studies have provided a strong rationale for including Bmi1-targeted therapy in the treatment strategies for patients presenting with malignancies displaying elevated Bmi1 expression.…”
Section: However In the Absence Of Bmi1 P16-mediated Inhibition Of supporting
confidence: 83%
“…More importantly, diminished Bmi1 levels reduced the self-renewal capacity of CSCs, which in turn correlated with lowered tumourigenic potential in vitro and in vivo. In keeping with the original observations, cells treated with a Bmi1 inhibitor became more apoptotic 77,[81][82][83] and underwent cell cycle arrest at G 0 phase. 81,82 Collectively, these studies have provided a strong rationale for including Bmi1-targeted therapy in the treatment strategies for patients presenting with malignancies displaying elevated Bmi1 expression.…”
Section: However In the Absence Of Bmi1 P16-mediated Inhibition Of supporting
confidence: 83%
“…Bmi1 knock-down also upregulated expression of p16, p19 and p53 tumor suppressor levels in transplanted tumors. 47 Our results therefore indicate that 1,25(OH) 2 D 3 prevents tumorigenesis by inactivating oncogenes such as Bmi1 which appear to play a key role in tumorigenesis. **p < 0.01; ***p < 0.001 compared to sh-control or the WT sh-control group.…”
Section: Discussionmentioning
confidence: 66%
“…Importantly, loss of C/EBPα in mouse respiratory epithelium led to respiratory failure at birth due to an arrest in the type II alveolar cell differentiation program [15]. Lung-specific C/EBPα knockout mice developed pulmonary adenocarcinoma, suggesting that the loss of C/EBPα could be an important event in the multistep process of lung tumorigenesis [19]. In this study, we found that C/EBPα expression was significantly decreased in lung adenocarcinoma tissues compared to para-carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Low expression levels of C/EBPα were found in 50% of stage II and IIIA lung adenocarcinomas, and induction of C/EBPα led to significant growth reduction attributable to proliferation arrest, morphological changes characteristic of differentiation and apoptosis [16-18]. A recent study also showed that C/EBPα was a tumor suppressor in lung cancer and that targeted B lymphoma Mo-MLV insertion region 1 homolog (BMI1) inhibition impaired tumor growth in lung adenocarcinomas with low C/EBPα expression [19]. C/EBP family members also regulate cell migration [20].…”
Section: Introductionmentioning
confidence: 99%